About one of the peculiar types of interrogative sentences (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the scientific viewpoints concerning a rhetoricquestion. In general, the nature of this question is closely connected withinterrogative sentences, though from the communicative point of view it isused to influence the communicator.The logical function is dependent on the form of the question, becausethe response is hidden in the form of a question. The positive form impliesa negative meaning and vice versa the negative form involves the positivemeaning. This type of question being interrogative by structure transmits aspecific message. Meanwhile, the main peculiar feature of it is a contradiction between form and content.
Keywords: rhetoric question; communicative and pragmatic element